Analysis of economic efficiency and optimization of drug supplies for the referral back program (PRB) in pharmacies for the first semester of 2025 - Puspitasari, Mitha Dwi (Borobudur Pharmacy Review, 2025)
Background: The sustainability of the Referral Back Program (PRB) is highly dependent on the financial viability of BPJS Kesehatan partner pharmacies. Economic efficiency, reflected in the margin between claim costs and drug procurement costs, is a crucial indicator for the operational sustainability of pharmacies in serving patients with chronic diseases. Objective: This study aims to analyze the level of economic efficiency of PRB implementation in pharmacies during the first semester of 2025 (January-June) and identify areas for inventory management optimization. Method: This study uses a quantitative descriptive approach. Economic efficiency is measured by analyzing the gross margin, which is the difference between the total costs approved (claims) by BPJS Kesehatan and the total purchase price of drugs from suppliers. Inventory analysis is performed using a combination of ABC-VEN methods to prioritize drug items based on investment value and clinical urgency. Claim and purchase data were analyzed monthly and in aggregate. Results: Data analysis showed that the average gross margin achieved by pharmacies during Semester I was 8.0%. Significant monthly margin fluctuations were found, with the lowest margin recorded in February (5.2%) and the highest margin in June (12.1%). ABC analysis showed that 4 of 19 drug items (21%) absorbed 81% of the total procurement budget. ABC-VEN analysis identified 4 drug items in the AV (Vital, High Value) category as the top priority for control. Conclusion: The implementation of PRB in pharmacies shows a positive and sustainable level of economic efficiency. However, the variability of margins between months and the concentration of investment value in several drug items indicate room for optimization through ABC-VEN data-based procurement strategies and price negotiations on Category A items to achieve more stable profitability.